Microfluidic Synthesis of Iron Oxide Nanoparticles - Matthew James; Richard A Revia; Zachary Stephen; Miqin Zhang (Nanomaterials, 2020)
Research efforts into the production and application of iron oxide nanoparticles (IONPs) in recent decades have shown IONPs to be promising for a range of biomedical applications. Many synthesis techniques have been developed to produce high-quality IONPs that are safe for in vivo environments while also being able to perform useful biological functions. Among them, coprecipitation is the most commonly used method but has several limitations such as polydisperse IONPs, long synthesis times, and batch-to-batch variations. Recent efforts at addressing these limitations have led to the development of microfluidic devices that can make IONPs of much-improved quality. Here, we review recent advances in the development of microfluidic devices for the synthesis of IONPs by coprecipitation. We discuss the main architectures used in microfluidic device design and highlight the most prominent manufacturing methods and materials used to construct these microfluidic devices. Finally, we discuss the benefits that microfluidics can offer to the coprecipitation synthesis process including the ability to better control various synthesis parameters and produce IONPs with high production rates.